Molecular requirements for safer generation of thrombolytics by bioengineering the tissue‐type plasminogen activator A chain. Issue 3 (13th March 2013) - Parcq, J.; Bertrand, T.; Baron, A. F.; Hommet, Y.; Anglès‐Cano, E.; Vivien, D.
Summary Background Thrombolysis with tissue‐type plasminogen activator (t‐PA) is the only treatment approved for acute ischemic stroke. Although t‐PA is an efficient clot lysis enzyme, it also causes damage to the neurovascular unit, including hemorrhagic transformations and neurotoxicity. Objectives On the basis of the mechanism of action of t‐PA on neurotoxicity, we aimed at studying the molecular requirements to generate safer thrombolytics. Methods We produced original t‐PA‐related mutants, including a non‐cleavable single‐chain form with restored zymogenicity (sc*‐t‐PA) and a t‐PA modified in the kringle 2 lysine‐binding site (K2*‐t‐PA). Both sc*‐t‐PA and K2*‐t‐PA showed fibrinolytic activities similar to that of wild‐type t‐PA on both euglobulin‐containing and plasma‐containing clots. In contrast to wild‐type t‐PA, the two mutants did not promote N‐methyl‐d‐aspartate receptor‐mediated neurotoxicity. Conclusions We designed t‐PA mutants with molecular properties that, in contrast to t‐PA, do not induce neurotoxicity.